Perfil ambiental da produção de leite orgânico no sudeste do Brasil - Pereira, Ana Flávia de Paula (2025)
In recent years, there has been an increased demand for information about the environmental impact of milk production systems. Given this reality, the organic milk market has grown globally, emerging as an alternative to more sustainable production systems. To evaluate the environmental impact of production systems, the Life Cycle Assessment (LCA) methodology was adapted to quantify emissions from dairy farms, both conventional and organic, and to compare these systems, elucidating sustainability data for the sector. In the present study, the LCA methodology was used to characterize organic milk production systems in southeastern Brazil and determine the environmental impact of 11 organic production units (OPUs), located in São Paulo (8), Minas Gerais (2), and Rio de Janeiro (1). The environmental impact categories determined in this study were: climate change potential, eutrophication, acidification, and land use. In terms of climate change potential, the results obtained were 1.408 (0.933 to 3.418) Kg of carbon dioxide equivalents (CO₂ eq)/Kg of fat and protein corrected milk (FPCM), with enteric methane emissions being the main contributor (75.5%), followed by off-farm feed production (11.3%) and manure management (8.7%). For water eutrophication potential, the values found were 1.13 (0.02 to 1.76) g phosphate equivalent (PO₄ eq)/Kg FPCM, mainly influenced by crop management. In terms of acidification potential, the values were 0.35 (0.01 to 1.05) g of sulfur dioxide equivalents (SO₂ eq)/Kg FPCM, with the main contributors being manure management and feed production. In the land use category, the values were 3.05 (0.73 to 15.7) m²/Kg FPCM. OPUs with lower production per animal showed worse results in the environmental impact categories. When compared to data from conventional farms, organic systems obtained similar or even higher results, questioning their efficiency in increasing sustainability. However, intensification and increased productivity showed potential to reduce environmental impacts.